Using high throughput screening to define virus clearance by chromatography resins. Issue 7 (26th March 2013) - Connell‐Crowley, Lisa; Larimore, Elizabeth A.; Gillespie, Ron
Abstract High throughput screening (HTS) of chromatography resins can accelerate downstream process development by rapidly providing information on product and impurity partitioning over a wide range of experimental conditions. In addition to the removal of typical product and process‐related impurities, chromatography steps are also used to remove potential adventitious viral contaminants and non‐infectious retrovirus‐like particles expressed by rodent cell lines used for production. This article evaluates the feasibility of using HTS in a 96‐well batch‐binding format to study removal of the model retrovirus xenotropic murine leukemia virus (xMuLV) from product streams. Two resins were examined: the anion exchange resin Q Sepharose Fast Flow™ (QSFF) and Capto adhere™, a mixed mode resin. QSFF batch‐binding HTS data was generated using two mAbs at various pHs, NaCl concentrations, and levels of impurities. Comparison of HTS data to that generated using the column format showed good agreement with respect to virus retentation at different pHs, NaCl concentrations and impurity levels. Results indicate that NaCl concentration and impurity level, but not pH, are key parameters that can impact xMuLV binding to both resins. Binding of xMuLV to Capto adhere appeared to tolerate higher levels of NaCl and impurity than QSFF, and showed some product‐specific impact on binding that was not observed with QSFF. Overall, the results demonstrate that the 96‐well batch‐binding HTS technique can be an effective tool for rapidly defining conditions for robust virus clearance on chromatographic resins. Biotechnol. Bioeng. 2013; 110: 1984–1994. © 2013 Wiley Periodicals, Inc.